2018
DOI: 10.1093/biolre/ioy264
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the NLRP3 inflammasome can prevent sterile intra-amniotic inflammation, preterm labor/birth, and adverse neonatal outcomes†

Abstract: Sterile intra-amniotic inflammation is commonly observed in patients with spontaneous preterm labor, a syndrome that commonly precedes preterm birth, the leading cause of perinatal morbidity and mortality worldwide. However, the mechanisms leading to sterile intra-amniotic inflammation are poorly understood and no treatment exists for this clinical condition. Herein, we investigated whether the alarmin S100B could induce sterile intra-amniotic inflammation by activating the NLRP3 inflammasome, and whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 144 publications
(177 reference statements)
9
72
0
1
Order By: Relevance
“…Consistent with the human findings, the depletion of Tregs during the third week of pregnancy induced preterm birth that was restored upon the adoptive transfer of such cells. The rates of preterm birth resulting from the depletion of Tregs were modest compared to animal models of systemic and local acute inflammation-induced preterm birth ( St Louis et al, 2016 ; Gomez-Lopez et al, 2016a , 2016b , 2018 , 2019 ; Garcia-Flores et al, 2018 ). However, this is consistent with the current belief that different subsets of preterm labor and birth are mediated through different mechanisms ( Romero et al, 2014a ).…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with the human findings, the depletion of Tregs during the third week of pregnancy induced preterm birth that was restored upon the adoptive transfer of such cells. The rates of preterm birth resulting from the depletion of Tregs were modest compared to animal models of systemic and local acute inflammation-induced preterm birth ( St Louis et al, 2016 ; Gomez-Lopez et al, 2016a , 2016b , 2018 , 2019 ; Garcia-Flores et al, 2018 ). However, this is consistent with the current belief that different subsets of preterm labor and birth are mediated through different mechanisms ( Romero et al, 2014a ).…”
Section: Discussionmentioning
confidence: 88%
“…This intraamniotic inflammatory response can result in deleterious effects on the offspring [27,28,[44][45][46][47][48][49]. Therefore, the elucidation of the mechanisms involved in intra-amniotic inflammation leading to preterm birth is critical for the development of novel treatment strategies to reduce adverse neonatal outcomes [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms leading to sterile intra-amniotic inflammation involve the activation of the NLRP3 inflammasome in the chorioamniotic membranes [81,82,85]. Indeed, animal experimentation has shown that alarmins (molecules that trigger sterile inflammation [225][226][227]) are capable of activating the NLRP3 inflammasome in the fetal membranes [228]. Importantly, these studies have generated promising data showing that, by tackling the activation of the NLRP3 inflammasome, sterile intra-amniotic inflammation can be treated and preterm birth prevented.…”
Section: Microbial Burden Correlated With Intra-amniotic Inflammasomementioning
confidence: 99%